KOSTERMANS SEVENTY-FIVE - Jacobs, M. (REINWARDTIA, 1982)
On 1 July 1981 Doc, as he is widely known, has reached the age of 75. Ten months earlier he returned from Ceylon to Bogor, his health restored, largely by his own efforts.